EFEKTIVITAS MODEL PEMBELAJARAN THINK, PAIR, SHARE TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA BERBANTUAN AUGMENTED REALITY KELAS X PADA MATA PELAJARAN SEJARAH DI MA AL-AMIN KAHU - Asgar, Andi (Journal of Innovation Research and Knowledge, 2025)
This research aims to evaluate the effectiveness of the think, pair, share learning model supported by augmented reality on students critical thinking abilities. The research design employed is a quasi-experimental approach, utilizing the Non-equivalent Control Group Design. The study was conducted at MA Al-Amin Kahu from August 01 to August 30, 2023. The population of the study comprised all 10th-grade students in the Science Program at MA Al-Amin Kahu. Two classes were selected as samples using purposive sampling where Class X Mipa 1 was designated as the experimental group and Class X Mipa 2 as the control group. Data were collected throught test and questionnaires. The analysis of the data revealed that the average pretest score for the experimental class was 63.77 while for the control class, it was 84.67. Meanwhile, the average posttest score for the experimental class increased to 82.22 and for the control class, it was 67.41. The analysis of prestest and posttest results from both classes indicated a significant influence on students critical thinking abilities and learning outcomes in the experimental class compared to the control class. Based on the results of the t-test calculation using SPSS, the critical thinking ability obtained a significance value of 0.00, which is less than 0.05 this implies that the Think, Pair, Share learning model supported by Augmented Reality is more effective in enhancing students critical thinking abilities.